2019
DOI: 10.1002/eco.2077
|View full text |Cite
|
Sign up to set email alerts
|

The test of the ecohydrological separation hypothesis in a dry zone of the northeastern Tibetan Plateau

Abstract: The ecohydrological separation hypothesis has generated considerable scientific interest and debate in ecohydrological studies, and it assumes there exist two water pools in subsurface water, one of which is soil water used by plants and the other is that supplied to groundwater. Although this hypothesis has been tested in several humid sites, a further test in arid and semiarid conditions is still needed. Based on the isotopic ratios in different water bodies collected during a 2-year field work, the hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Plants can access shallow and deep soil water, as well as groundwater with a tendency to prioritize the use of stable and continuous water sources (Zhao & Wang, ), at least in regions where some sources are continuously available. Several studies based on an isotope approach and focusing on the identification of different water sources accessed by plants have been conducted at individual sites in many regions of the world and on different plant species (e.g., to name a few recent studies, Allen, Kirchner, Braun, Siegwolf, & Goldsmith, ; Chi, Zhou, Yang, Li, & Zheng, ; Dubbert, Caldeira, Dubbert, & Werner, ; Evaristo et al, ; Nie et al, ; Oerter, Siebert, Bowling, & Bowen, ; Qiu et al, ). Recent meta‐analyses assessed plant water sources across different biomes and plant species (Barbeta & Peñuelas, ; Evaristo, Jasechko, & McDonnell, ; Evaristo & McDonnell, , ).…”
Section: Introductionmentioning
confidence: 99%
“…Plants can access shallow and deep soil water, as well as groundwater with a tendency to prioritize the use of stable and continuous water sources (Zhao & Wang, ), at least in regions where some sources are continuously available. Several studies based on an isotope approach and focusing on the identification of different water sources accessed by plants have been conducted at individual sites in many regions of the world and on different plant species (e.g., to name a few recent studies, Allen, Kirchner, Braun, Siegwolf, & Goldsmith, ; Chi, Zhou, Yang, Li, & Zheng, ; Dubbert, Caldeira, Dubbert, & Werner, ; Evaristo et al, ; Nie et al, ; Oerter, Siebert, Bowling, & Bowen, ; Qiu et al, ). Recent meta‐analyses assessed plant water sources across different biomes and plant species (Barbeta & Peñuelas, ; Evaristo, Jasechko, & McDonnell, ; Evaristo & McDonnell, , ).…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al, (2019) showed that trees transpire water from first rainfall event that recharged soil water storages during the wet season, and supported transpiration during the dry season. While some synthesis (e.g., J. Evaristo, Jasechko, et al, 2015) and field‐based investigations have found that the use of tightly bound water by trees is widespread across different biomes (G. R. Goldsmith, Muñoz‐Villers, et al, 2012; Hervé‐Fernández et al, 2016), others have not (Geris et al, 2015; Qiu et al, 2019). Nevertheless, the mechanisms governing tree water source apportionment are still unclear (Berry et al, 2017; Penna et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The development of low-cost and easy-to-use spectroscopic techniques for the collection and isotopic analysis of water samples at a high temporal resolution (e.g., Kerstel et al, 1999;Penna et al, 2010;von Freyberg et al, 2017) stimulated the application of stable isotopes to investigate the water fluxes in the soil-plant-atmosphere continuum (Brooks et al, 2010;McDonnell, 2014). An increasing number of new studies has been conducted to better understand water dynamics, such as water uptake and evapotranspiration partitioning, in the soil-plant-low atmosphere continuum in different climates and in both natural (e.g., Allen et al, 2019;Dubbert et al, 2019;Liu et al, 2019a;Oerter et al, 2019;Qiu et al, 2019) and managed (agricultural and agroforest) (e.g., Liu et al, 2019b;Quade et al, 2019;Zhang et al, 2019;Penna et al, 2020) environments. Compared to the rapid increase of the number of studies using a stable isotope approach, only a small fraction of them focused on the comparison of two or more soil or plant water extraction techniques (Sprenger et al, 2015;Orlowski et al, 2016b;Millar et al, 2018;Fischer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%